(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Literary trends as realism and naturalism have played a significant role in the development of XX century American Literature. While realists described events based on the observation and reflection of the details of the daily events, the advancements in science, especially Darwin’s teachings, introduced new ideas and perspectives in literature which led to emergence of naturalism in XX century American naturalism. The following paper discusses factors that led to American realism and naturalism, representatives that significantly contributed to the development of the literature.